“It’s like your body is fighting against you”: a cross-sectional qualitative interview study of quality of life in U.S. Black women diagnosed with endometriosis - Whitney S. Rice; Melanie Dakwa; Sofia Filippa; Ashi Parikh; Subasri Narasimhan (BMC Women's Health)
Abstract Background Endometriosis is a chronic gynecological condition that significantly affects quality of life in an estimated 10–15% of women of reproductive age, yet Black women in the United States remain underrepresented in endometriosis research, limiting the potential for application of innovation and discovery. This study addresses this critical gap in the literature by exploring the quality of life experiences of U.S. Black women with endometriosis. Methods Using a cross-sectional qualitative design, this study collected data from in-depth semi-structured interviews with 16 Black women aged 18–45 diagnosed with endometriosis from September-October 2021. Participants were recruited via purposive and snowball sampling through online platforms. Interviews explored the physical, psychosocial, and healthcare-related dimensions of quality of life, as well as perceptions of self-advocacy and resilience, and were video and audio recorded on Zoom and transcribed verbatim. Thematic data analysis was employed to generate themes. Results Participants were regionally diverse, with most (44%) from the South and most (69%) were diagnosed by a medical professional. Five major themes emerged: (1) debilitating physical symptoms (blood clots, constipation, urogenital pain, etc.), (2) psychosocial impacts including emotional distress, social isolation, and altered self-perception, (3) complex and often negative healthcare navigation experiences, (4) the dual burden and empowerment of self-advocacy and resilience, and (5) lessons learned and calls to action for improved care. Conclusions This study offers a novel and nuanced sense of Black women’s quality of life with endometriosis, including the intersecting physical, emotional, and structural factors that shape their experiences, and the deepened sense of strength and agency developed though them. The findings underscore the urgent need for culturally responsive, patient-centered care and consideration of Black women’s voices in recommended pathways for future endometriosis research and more equitable clinical practice.